Pelatihan Budidaya Kakao Guna Peningkatan Kapasitas Petani Dan Peningkatan Produksi Kakao Di Aceh Utara - Nazaruddin, Muhammad; Yunus, Saifuddin; Baidhawi, Baidhawi; Murdani, Murdani (Jurnal Malikussaleh Mengabdi, 2023)
Cocoa is one of the dominant plantation crops in North Aceh. Matangkuli District is a cocoa development area in North Aceh. The planting area is satisfactory, but the yield and quality are still below the national average. The general objective of this activity is to build and foster a farming community through the cocoa commodity business in order to produce reliable quality human resources. Reliable human resources will be able to manage all the potential of existing natural resources in order to produce quality cocoa bean production, both in terms of production and productivity, so as to create added value and competitiveness according to market needs. In addition, in the long term it is hoped that through this activity it will be able to increase people's income and create jobs and be able to increase the competitiveness of the cocoa value chain by providing more business opportunities in the cocoa plantation sub-sector within the North Aceh Regency area, especially Gampong Ceubrek District. Matangkuli. The focus of the implementation of this service is increasing the capacity of knowledge and skills in managing cocoa gardens and plants, rejuvenating old plants, and improving the quality of crops. During extension activities and field practice, cocoa farmers have been able to practice cocoa maintenance, plant rejuvenation and post-harvest fruit treatment practices. At least the farmer groups will make a pilot demonstration plot to apply maintenance, rejuvenation and post-harvest treatment which will then be compared with the results achieved conventionally. In addition, cocoa farmers are also trained in managing farmer groups. Where the harvest will be concentrated to be given fermentation and drying treatment simultaneously. Marketing will be done collectively, not individually. Collective sales will save on transportation costs, so the sales value received will be higher.